Evidence of Floral Reversion during In vitro Shoot Regeneration from Young Inflorescence of the Medicinal Geophyte Gloriosa superba L. (Plant Tissue Culture and Biotechnology, 2013)
Plant Tissue Cult. & Biotech. 23(1): 115?120, 2013 (June)DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15568